2021
DOI: 10.1177/1069072721995698
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Demographic Differences in Work as a Calling in the United States: Results From a Nationally Representative Sample

Abstract: Within the last two decades, social science research on work as a calling has rapidly grown. To date, knowledge regarding prevalence and demographic differences of calling in the United States derives from data collected mainly from regionally limited and/or occupationally homogenous samples. The present study used data from the Portraits of American Life Study, a nationally stratified panel study of religion in the United States (U.S.), to estimate calling’s prevalence in the U.S. Our findings represent the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The Portraits of American Life Study produced data estimating that 43% of U.S. adults either “mostly” or “totally” agree that they “have a calling to a particular kind of work” (White et al, 2021, pp. 1, 17).…”
Section: Background To the Studymentioning
confidence: 99%
“…The Portraits of American Life Study produced data estimating that 43% of U.S. adults either “mostly” or “totally” agree that they “have a calling to a particular kind of work” (White et al, 2021, pp. 1, 17).…”
Section: Background To the Studymentioning
confidence: 99%
“…One such resource is an individual’s experience of living a calling (i.e., a sense of transcendent summons, meaning, and prosocial orientation in one’s work; Duffy & Dik, 2013 ). A recent population estimate found that 43% of U.S. adults endorsed the statement “I have a calling to a particular kind of work” as either mostly or totally true of them ( White et al, 2021 ), underscoring the prevalence of calling. Living a calling may serve as a personal resource which enables individuals to gain other personal resources (e.g., self-efficacy, competence, and motivation) that can be useful for dealing with intensifying job demands and adapting to changing work circumstances.…”
mentioning
confidence: 99%